2018
DOI: 10.1038/s41598-018-22585-2
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and expression analyses of genes involved in raffinose accumulation in sesame

Abstract: Sesame (Sesamum indicum L.) is an important oilseed crop. However, multiple abiotic stresses severely affect sesame growth and production. Raffinose family oligosaccharides (RFOs), such as raffinose and stachyose, play an important role in desiccation tolerance of plants and developing seeds. In the present study, three types of key enzymes, galactinol synthase (GolS), raffinose synthase (RafS) and stachyose synthase (StaS), responsible for the biosynthesis of RFOs were identified at the genome-wide scale in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 52 publications
5
36
0
Order By: Relevance
“…The phylogenetic analysis of putative RFO-related proteins from Fabaceae, including these five enzyme families identified in wild Arachis, showed a clear subdivision within each family, supported by high bootstrap values. This clustering, based on phylogenetic proximity, was related to the intron/exon organization of the corresponding Arachis genes, as previously observed for other plant species [8][9][10] . Similarly to the conservation of gene structure, amino acid sequences were highly conserved too, for example, the hydrophobic pentapeptide (APSAA), characteristic of the GolS family 42 , was found for all the proteins from A. duranensis and A. ipaënsis, as well as other conserved motifs in the different enzyme families.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The phylogenetic analysis of putative RFO-related proteins from Fabaceae, including these five enzyme families identified in wild Arachis, showed a clear subdivision within each family, supported by high bootstrap values. This clustering, based on phylogenetic proximity, was related to the intron/exon organization of the corresponding Arachis genes, as previously observed for other plant species [8][9][10] . Similarly to the conservation of gene structure, amino acid sequences were highly conserved too, for example, the hydrophobic pentapeptide (APSAA), characteristic of the GolS family 42 , was found for all the proteins from A. duranensis and A. ipaënsis, as well as other conserved motifs in the different enzyme families.…”
Section: Discussionsupporting
confidence: 80%
“…Conversely, the genes from the GolS family have undergone duplication mostly by WGD and can be observed in gene blocks in two different chromosomes. Other studies also found that segmental duplications were the driving force for the expansion of GolS genes in S. indicum and Rosaceae genomes, being associated with a possible subfunctionalization 10,12 .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…13 cultivar were grown hydroponically in a growth chamber (16 h light/8 h dark cycle at 28°C). Two-week old seedlings were exposed to different abiotic stresses including osmotic, salt, and cold treatments as described in our previous study [ 52 ]. The shoots of seedlings with different treatments were harvested at 0, 2, 6 and 12 h after treatment.…”
Section: Methodsmentioning
confidence: 99%
“…The chromosomal location information of watermelon Dof genes was obtained from the watermelon genome database, and MapChart was used to display the physical positions of all ClDof genes along each chromosome. Gene duplications were examined using multiple collinear scanning toolkits (MCScanX) software with the default parameters as previously reported (You et al, 2018).…”
Section: Chromosomal Location and Duplication Analysismentioning
confidence: 99%